Requirements for the import of neisserial Omp85 into the outer membrane of human mitochondria - Ott, Christine (Portland Press Ltd., 2013)
β-Barrel proteins are present only in the outer membranes of Gram-negative bacteria, chloroplasts and mitochondria. Fungal mitochondria were shown to readily import and assemble bacterial β-barrel proteins, but human mitochondria exhibit certain selectivity. Whereas enterobacterial β-barrel proteins are not imported, neisserial ones are. Of those, solely neisserial Omp85 is integrated into the outer membrane of mitochondria. In this study, we wanted to identify the signal that targets neisserial β-barrel proteins to mitochondria. We exchanged parts of neisserial Omp85 and PorB with their Escherichia coli homologues BamA and OmpC. For PorB, we could show that its C-terminal quarter can direct OmpC to mitochondria. In the case of Omp85, we could identify several amino acids of the C-terminal β-sorting signal as crucial for mitochondrial targeting. Additionally, we found that at least two POTRA (polypeptide-transport associated) domains and not only the β-sorting signal of Omp85 are needed for its membrane integration and function in human mitochondria. We conclude that the signal that directs neisserial β-barrel proteins to mitochondria is not conserved between these proteins. Furthermore, a linear mitochondrial targeting signal probably does not exist. It is possible that the secondary structure of β-barrel proteins plays a role in directing these proteins to mitochondria.